(untitled) (Journal of Nepal Physical Society, 2020)
Computational calculation of energy loss and study of damage profiles during ionic implantation by gallium ions on germanium had been carried out. The required energies for doping of gallium ion on germanium, in order to obtain maximum damage at 600 Å, were calculated using SRIM; Stopping and Range of Ions in Matter. The ions when implanted independently on germanium causes the production of germanium recoils, vacancy-interstitial pairs, and phonons during the collision process. For 130 keV gallium ion, the energy used for ionization, phonon production and vacancies creation are 37.713 keV (29.01% of incident energy), 90.006 keV (64.29% of incident energy) and 8.71 keV (6.7% of incident energy) respectively. The amount of target displacement, replacement collisions and vacancies were also evaluated. Doping of gallium ions on germanium also reveals that the energy loss due to nuclear stopping was greater than electronic stopping.